Footloose multinationals? - Holger Görg; Eric Strobl (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2001)
This paper examines whether multinational companies are more footloose than their domestic counterparts in the host country, using data for the Irish manufacturing sector. First, we investigate whether survival rates differ between multinationals and indigenous plants. Second, we analyse whether employment is more unstable in multinationals compared to indigenous firms. As regards the first aspect we find that multinationals are more likely to exit the market than indigenous plants when controlling for other plant and industry specific characteristics. In terms of employment persistence we find that new jobs generated in MNCs appear to be more persistent than jobs generated in indigenous firms. Also, MNCs are quicker to recover lost jobs than are indigenous firms.
Keywords: 330; Multinationales Unternehmen; Personalbedarf; Volatilität; Verarbeitendes Gewerbe; Irland